Optimal parameters of dental ultrasonic instrument diamond coating for enamel removal - Yunn-Shiuan Liao; Ting-Chang Lin; Ming-Shu Lee; Po-Yuan Su; Yen-Liang Chen; Hao-Hueng Chang; Chun-Pin Lin (Elsevier, 2015)
Background/purpose: Ultrasonic instruments are commonly used in dentistry because of their safety, acceptance by patients, ease of viewing the surgical area, and highly precise cutting. However, they do not efficiently remove enamel. The aim of this study is to optimize the surface coating parameters of an ultrasonic diamond grinding tip for enamel removal. Materials and methods: The experiments were conducted using a triple-axle precision moving platform. The ultrasonic handpiece was mounted on the platform column, and powered by an ultrasonic device with a voice coil motor providing a uniform down force of 2 N to grind adult molar specimens. The commercially available diamond tips UL3A (Cur scaler, Bonart, Taiwan) and EX1 (Newtron, Acteon, France) were used in this study. The Taguchi method and analysis of variance were used to determine the optimal surface parameters (mesh size, crystal shape, protrusion, and crystal density) of dental diamond tips. By using the optimal surface characteristics, new tips N1 and N2, having the same geometrical shape and dimension of UL3A and EX1, respectively, were fabricated and their grinding performance was tested. Results: The optimal enamel removal parameters of the grinding tip are diamonds of 100/120 mesh size, shape of well-formed crystal facet, 75 μm protrusion, and density of 45 crystals per square millimeter surface area. The material removal rate (MRR) of enamel for N1 (UL3A with new characteristics) is 0.064 mm3/s, 3.4 times that of the original UL3A tips. For N2 (EX1 with new characteristics) it is 0.126 mm3/s, which is 3.2 times that of the original EX1 tips. Conclusion: Protrusion, shape, and density of diamonds of an ultrasonic dental tip are significantly related to the MRR of enamel, and the optimal combination of these parameters is obtained. Knowledge of the importance of these variables will help in more effective use of the ultrasonic technology in dentistry.